Inflammatory ulcera caused of vasculitides and vasculopathy - Lutze, S.; Kaisermayer, E. S.; Daeschlein, G.; Jünger, M. (Phlebologie, 2015)
In addition to traditional vascular causes ulceration of the lower leg as peripheral arterial disease and chronic venous insufficiency, it is primarily the vasculitis and vasculopathies, often are both diagnostically and therapeutically to a challenge.The disorder group ranked in the frequency distribution of the causes of a leg ulcer with <10 % rarely in the area, but is much more complex of the pathogenesis, the clinical picture, the course of therapy and often much more complex.The revised International in 2012 Chapel Hill Consensus Conference (CHCC) Nomenclature of vasculitis is a first impression of the diversity of this group of diseases and makes it clear how important the medical history for diagnosis is.In the CHCC- categorizing the etiology, pathogenesis, the caliber of the vessel, the inflammatory type, the organs mainly affected, the clinical manifestation, genetic predisposition and demographic parameters were included.With this revision of the first CHCC nomenclature of 1994 took place an important adaptation to the latest findings. The group of vasculitis is divided specific, this facilitates the handling of the disease in clinical practice.The vasculopathies represent another rare fringe of the causes of an ulcer curis. These disorders are often as complex as a vasculitis and must be always used in difficult to treat ulcers in the differential diagnosis.Neben den klassischen vaskulären Ursachen von Ulzerationen an den Unterschenkel wie einer peripheren arteriellen Verschlusskrankheit und der chronisch venösen Insuffizienz sind es vor allem die Vaskulitiden und Vaskulopathien, die sowohl diagnostisch als auch therapeutisch oft zu einer Herausforderung werden. Die Erkrankungsgruppe rangiert in der Häufigkeitsverteilung der Ursachen eines Ulcus cruris mit <10 % eher im Bereich selten, ist aber von der Pathogenese, vom klinischen Bild, dem Verlauf und der Therapie oft wesentlich komplexer.Die in 2012 überarbeitete internationale Chapel Hill Consensus Conference (CHCC) Nomenklatur der Vaskulitiden gibt einen ersten Eindruck über die Mannigfaltigkeit dieser Erkrankungsgruppe und macht deutlich wie wichtig hierbei die Anamnese zur Diagnosefindung ist. In die CHCC-Kategorisierung flossen die Ätiologie, die Pathogenese, das Kaliber des Gefäßes, der Entzündungstyp, die hauptsächlich betroffenen Organe, die klinische Manifestation, genetische Prädisposition und demografische Parameter mit ein.Mit dieser Revision der ersten CHCC-Nomenklatur von 1994 fand eine wichtige Adaptierung an die neusten Erkenntnisse statt. Die Gruppe der Vaskulitiden wird spezifischer eingeteilt, dies erleichtert den Umgang mit dem Krankheitsbild im klinischen Alltag.Die Vaskulopathien stellen eine weitere seltene Randgruppe innerhalb der Ursachen eines Ulcus curis dar. Diese Erkrankungen sind oft ebenso komplex wie eine Vaskulitis und müssen bei schwierig zu behandelnden Ulcera immer als Differenzialdiagnose mit herangezogen werden.
Keywords: Vasculitis; vasculopathy; ulcer cruris